OPTIMIZATION BASED ON COLLECTIVE INTELLIGENCE OF A SWARM OF PARTICLES WITH CONTROL OF THEIR SPEED CHANGE - Oleynik, A. A.; Subbotyn, S. A. (Radio Electronics, Computer Science, Control, 2024)
A particle swarm optimization method has been considered. A modification of PSO-method with velocity control has been developed. The experiments on finding global optimum for multidimensional function on the basis of suggested modification has been carried out.